Gut Microbiome Alterations in Men Who Have Sex with Men-A Preliminary Report - Lu, Xiaoyan; Zhang, Kexin; Wang, Tianli; Zhang, Xueqing; Zhang, Jianghui; Wei, Hongyuan; Gao, Pan; Wang, Jun; Zhang, Hongbo; Zhang, Zhihua (Current HIV Research, 2022)
Background: Studies have found that HIV is mainly transmitted through the mucosal surface, and the entrance of early progression of the disease is the rectal and colonic mucosa. So, this paper aimed to explore and analyze the structural differences of gut microbiome between men who have sex with men (MSM) and those who don’t have sex with men (Non-MSM), expecting to find novel biological factors that potentially impact transmission and/or disease in MSM population. Methods: We collected a total of 33 stool samples, 16 were MSM and 17 were Non-MSM. The 16S rRNA gene amplification sequencing was used to detect the alteration and structure of the gut microbiome community in two groups. Results: The difference in β diversity of gut microbiome of two groups of subjects was statistically significant (P<0.001), indicating that the difference in the structure of the gut microbiome of two groups was statistically significant. Compared with the phylum and genus level of Non-MSM group, the relative abundances of Actinobacteria, Proteobacteria, genera Collinsella, Prevotella, Bifidobacterium and Ralstonia in MSM group were higher (P<0.001, P<0.05, LDA score (log10)>2), and the relative abundance of Bacteroidetes, genera Erysipelotrichaceae incertae sedis, Bilophila, Holdemania, Clostridium XIVb and Bacteroidaceae in MSM group were lower (P<0.01, LDA score (log10)>2). Conclusion: There are some differences in the structure of gut microbiome between MSM group and Non-MSM group. It indicates the differences in behavior and characteristics between MSM and Non-MSM populations may be related to the difference in the structure of gut microbiome.
Keywords: 16S rRNA